LOPH and D-MHC in the Treatment of FeLV Associated Acute Leukemia in a Cat - Horta, Rodrigo dos Santos; Ferreira, Ana Luisa Fajardo; Costa, Mariana de Pádua; Frossard, Ligia Soares; Nimrichter, Júlia Campero; de Carli, Mylena Duarte; de Oliveira Paes, Paulo Ricardo (Acta Scientiae Veterinariae, 2021)
Background: Bone marrow primary malignancies are denominated leukemias, classified as myeloid or lymphoid, according to the cell lineage, and acute or chronic, according to the cell´s state of maturation. In cats, acute lymphoid leukemia is the most common form, especially in regions endemic for feline leukemia virus and / or feline immunodeficiency virus. A new treatment protocol for lymphomas, called LOPH, has been described for animals with FeLV persistent viremia. This study aimed to report a case of a cat presenting with FeLV associated acute leukemia and treated with the LOPH protocol, and, in the rescue phase, a modification of the D-MAC protocol, denominated D-MHC. Case: A 4-year-old mixed breed intact queen was attended due to lethargy and inappetence. The patient did not present any relevant abnormalities in the clinical exam and complementary exams were performed including complete blood count, biochemical profile, SNAP Feline Triple Test, chest radiographs and abdominal ultrasound. Imaging tests and biochemical values were unremarkable, but the patient presented a reagent result for FeLV and severe leukocytosis due to lymphocytosis. The morphological evaluation of the blood smear revealed the presence of blasts, in a concentration greater than 20% of the nucleated cells, which allowed the characterization of a leukemic state, probably lymphoid. First-line treatment was based on the LOPH protocol, including Lomustine, Vincristine, Prednisoloneand Doxorubicin, in four-week cycles. Nevertheless, during the third cycle, 66 days after the institution of this protocol, the patient presented a febrile condition along with marked leukocytosis due to lymphocytosis, confirming leukemia recurrence. A rescue attempt was performed with a modification of the D-MAC protocol, originally consisting of the combination of dexamethasone, melphalan, actinomycin-D and cytarabine, but with replacement of actinomycin-D by doxorubicin, and therefore nominated D-MHC. After the three cycles there was a return of the febrile condition associated with severe pancytopenia and euthanasia was elected due to poor clinical condition, resulting in a survival time of 124 days. The hematological toxicity of the induction protocol included anemia and neutropenia, with mainly grade I events, but with the occurrence of a grade IV event. The adverse effects of the rescue protocol were similar, but with a greater number of grade IV events. Discussion: FeLV is considered the most lethal retrovirus of the domestic cat, with a major impact on health and life expectancy. Persistent FeLV antigenemia increases the risk of hematopoietic neoplasms in 62.1 times due to a direct insertional mutagenesis. In endemic regions, approximately 70% of cats with acute leukemia have persistent FeLV antigenemia, as the patient in this report. The diagnosis was made through association of retroviral status and the identification of more than 20% of blasts, possibly lymphoblasts, in the blood stream, sparing the need for a myelogram. Considering the poor prognosis for acute lymphoid leukemias and the patient’s retroviral status, treatment was initiated with the LOPH protocol, including lomustine, as a potent agent to induce remission, and doxorubicin, which can result in longer remission intervals. After 66 days free of the disease, the patient presented recurrence of the leukemic condition, starting the rescue protocol D-MHC. Remission was again obtained with duration similar to the first protocol, however, on the occasion of a new leukemia recurrence, euthanasia was elected. The treatment adopted for the patient in this report resulted in a longer survival time than reported in other studies. Despite the aggressiveness of the protocols, especially the D-MHC, it was possible to perform it using the monocyte and granulocyte stimulation factor to reverse neutropenia.